THE ROLE OF RADIO AND TELEVISION COMMERCIALS AND INTERNET IN THE PROMOTION ACTIVITIES OF SEED COMPANIES ON POLISH MARKET - Bralewski, Tomasz; Hołubowicz, Roman (Acta Scientiarum Polonorum. Oeconomia, 2005)
The aim of research carried out in the years 2001–2005 was to characterize the role of radio, television and Internet in promotion activities of seed companies acting on Polish market. The seed companies used in their marketing activities emitted spots – through these three media. They appreciated the role of Internet creating page centers of WWW, sometimes including a few hundred webpages. Similarly to catalogues, transmitted information depended upon promotion policy of particular companies. However, they underestimated possibility of selling seeds through the Internet. Only one Polish seed company was running the Internet shop offering in it its products.